Quality of life, firm productivity, and the value of amenities across Canadian cities - David Albouy; Fernando Leibovici; Casey Warman (Queen's University, Department of Economics, 2012)
This paper presents the first hedonic general-equilibrium estimates of quality-of-life and firm productivity differences across Canadian cities, using data on local wages and housing costs. These estimates account for the unobservability of land rents and geographic differences in federal and provincial tax burdens. Quality-of-life estimates are generally higher in Canada's larger cities: Victoria, Vancouver are the nicest overall, particularly for Anglophones, while Montreal and Ottawa are the nicest for Francophones. These estimates are positively correlated with estimates in the popular literature and may be explained by differences in climate. Toronto is Canada's most productive city; Vancouver, the overall most valued city.
Keywords: H24; H5; H77; J61; R1; 330; quality of life; firm productivity; cost-of-living; firm productivity; compensating wage differentials; Ballungsraum; Lebensqualität; Produktivität; Lohnniveau; Immobilienpreis; Kanada